Effect of maternal lactoferrin supplementation on iron contents and anti-oxidant capacity in Dahe black Pig neonates - Zhang, Chunyong; Li, Cenxi; Xing, Xiaokun; Ji, Peng; Li, Meiquan; Pan, Hongbin; Guo, Rongfu; An, Qingcong (Frontiers in Veterinary Science, 2022)
Iron levels are closely related to animals' growth performance and anti-oxidant function. Lactoferrin (LF) is an iron-binding glycoprotein, which can promote the absorption of iron and regulate immune function. This study aimed to clarify the effect of maternal LF supplementation on the iron metabolism of Dahe piglets. Sixty sows (Dahe black, parity 3-4, no significant differences in body weight) were randomly assigned to five groups: control (basal diet with no iron supplementation), supplemented 100 (LF1 group), 200 (LF2 group), or 300 (LF3 group) mg LF/kg in the basal diet, and the basal diet supplemented with 100 (Fe-Gly group) mg Fe/kg as ferrous glycine (Fe-Gly). The serum anti-oxidant parameters of the sows and neonatal piglets were determined. The iron contents, anti-oxidant gene expression levels, and Fe-acquisition genes were detected in the liver, heart, spleen, and other neonatal organs. The results indicated that (1) the LF3 group of sows had the highest serum and colostrum iron contents (P < 0.05). The maternal LF significantly promoted the iron stores in the heart, liver, spleen, and lung of piglets compared with Fe-Gly. (2) The maternal LF increased serum glutathione peroxidase (GSH-Px) and total superoxide dismutase (T-SOD) activities of sows. Compared with other groups, the total anti-oxidant capacity (T-AOC) activity of LF2 groups increased significantly (P < 0.05). (3) LF significantly increased piglet serum GSH-Px, T-SOD, and T-AOC activities (P < 0.05). (4) Gene expression levels of GSH-Px, and SOD in the duodenum and jejunum of the LF2 group were significantly higher than in the Fe-Gly group (P < 0.05), while the expression levels in the liver and heart were lower (P < 0.05). (5) The expression levels of hepcidin and LF in the liver and duodenum of the LF2 group were significantly higher than in the Fe-Gly group (P < 0.05). In conclusion, maternal LF supplementation showed remarkable effects on iron storage in neonatal piglets, and exhibited strong antioxidant activities, it is helpful to prevent the occurrence of iron deficiency, and improves the immune function of animals.